Co-occurrence of Carpenter syndrome and double outlet right ventricle - Osman Güvenç; Derya Çimen; Derya Arslan; İbrahim Güler (KARE Publishing, 2017)
Carpenter syndrome (Acrocephalopolysyndactyly type 2, OMIM 201000) is a rarely seen autosomal recessive disorder. In addition to abnormalities such as acrocephaly, craniosynostosis, facial asymmetry, polydactyly and syndactyly, obesity, hypogonadism, mental retardation, and corneal opacity, it may frequently be accompanied by congenital heart diseases such as ventricular septal defect, patent ductus arteriosus and pulmonary stenosis. Double outlet right ventricle is a defect in which both major arteries originate in the morphological right ventricle. To the best of our knowledge, this is the first report in the literature of double outlet right ventricle disease in combination with Carpenter syndrome.